2010
DOI: 10.1097/brs.0b013e3181d1049f
|View full text |Cite
|
Sign up to set email alerts
|

Early Rehabilitation Targeting Cognition, Behavior, and Motor Function After Lumbar Fusion

Abstract: The study shows that postoperative rehabilitation can be safely implemented during the first 3 months after lumbar fusion and should include measures to modify psychological as well as motor functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
169
8
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(195 citation statements)
references
References 45 publications
13
169
8
5
Order By: Relevance
“…Furthermore, strong influences and mediation roles of psychological factors on pain, mental health, fear of movement/(re)injury, disability and HRQOL in patients scheduled for lumber fusion have been shown [1]. In addition to our own observations in a randomised controlled trial [2], a previous study showed the importance of post-operative rehabilitation for the outcome of lumbar fusion [4]. In both trials, biopsychosocially orientated rehabilitation was more effective than exercise therapy in improving functional outcome [2,4].…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Furthermore, strong influences and mediation roles of psychological factors on pain, mental health, fear of movement/(re)injury, disability and HRQOL in patients scheduled for lumber fusion have been shown [1]. In addition to our own observations in a randomised controlled trial [2], a previous study showed the importance of post-operative rehabilitation for the outcome of lumbar fusion [4]. In both trials, biopsychosocially orientated rehabilitation was more effective than exercise therapy in improving functional outcome [2,4].…”
Section: Introductionsupporting
confidence: 52%
“…In 99 of the patients, decompression was performed by full laminectomy and partial facet joint resection in central spinal stenosis and spondylolisthesis (isthmic and degenerative) or by partial facet joint resection in root canal stenosis. The patients participated in a randomised controlled trial analysing the short-and long-term effectiveness of a psychomotor therapy (N = 53) compared with an exercise therapy (N = 54) applied during the first 3 months after lumbar fusion [2]. Psychomotor therapy combined cognitivebehavioural and motor relearning strategies to modify maladaptive pain cognitions, behaviour and motor control.…”
Section: Study Design and Selection Of Patientsmentioning
confidence: 99%
“…Thus far, a limited number of randomised controlled trials (RCTs) have been published and the evidence of exercise therapy in restoring the spinal functioning and improving disability or HRQoL after fusion surgery is weak [10][11][12][13][14][15][16]. The commencement time and structure of the rehabilitation programs in previous RCT's varies [10][11][12][13][14]17].…”
Section: Introductionmentioning
confidence: 99%
“…The commencement time and structure of the rehabilitation programs in previous RCT's varies [10][11][12][13][14]17]. Most trials were implemented close to time of surgery, starting preoperatively [13,14], during hospital stay or soon after discharge [10,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation